2010
DOI: 10.1002/jbm.a.32713
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and polymer film thickness effects on endothelial cell adhesion and proliferation

Abstract: Adherence and growth rates of human aortic endothelial cells (HAEC) on plasma polymerized poly (vinylacetic acid) films were measured as functions of the surface density of -COOH groups and plasma deposited film thickness. Pulsed plasma polymerization was employed to produce films containing 3.6 to 9% -COOH groups, expressed as a percent of total carbon content. Endothelial cells exhibited increased cell adherence and proliferation with increasing -COOH surface densities. Additionally, and unexpectedly, cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Here, higher crosslinking of the hydrogel led to higher cell adhesion. This may be explained by the different surface properties of the two hydrogels like the wettability [20] or surface roughness, which change during degradation processes [21]. Additionally, available data imply that also the higher substrate stiffness of G10_LNCO8 supports cell adhesion [22].…”
Section: Endothelial Cell Functionmentioning
confidence: 99%
“…Here, higher crosslinking of the hydrogel led to higher cell adhesion. This may be explained by the different surface properties of the two hydrogels like the wettability [20] or surface roughness, which change during degradation processes [21]. Additionally, available data imply that also the higher substrate stiffness of G10_LNCO8 supports cell adhesion [22].…”
Section: Endothelial Cell Functionmentioning
confidence: 99%
“…Previous studies have shown that carboxylic acid groups play an important role in the attachment and migration of various cell types. [ 53 ] In addition, a balance between hydrophilicity and hydrophobicity is required for optimal cell-surface interactions. [ 54 ] Arima and Iwata reported that surface wettability in addition to the functional groups (e.g., carboxylic acid and amine groups) plays a signifi cant role in the adherence of cells.…”
Section: Full Papermentioning
confidence: 99%
“…Successful PCR amplification was detected from as small as 50 l of sample (lane 1), while at least 200 l urine was needed to generate enough PCR templates in a similar report [25]. This high extraction performance can be ascribed to the carboxylated surfaces of the nanoparticles, which bind mammalian cells with a high affinity [14,24,25,35,36], especially when used with the binding buffer employed in the present study. The higher surface area:volume ratio and good dispersal properties inherent to the nanoparticles employed in this study conferred an advantage over commonly used micro-sized particles, as evidenced by their superior binding capabilities with mammalian cells.…”
Section: Resultsmentioning
confidence: 75%